Weed management using crop competition in Pakistan: A review. (May 2017) - Ali, Hafiz Haider; Peerzada, Arslan Masood; Hanif, Zarka; Hashim, Saima; Chauhan, Bhagirath Singh
Abstract: Agriculture occupies an important place in improving the living standards of farmers in Pakistan. About 90% of farm earnings rely on the cultivation of sugar, fibre, cereals and legumes. Due to lack of essential resources and technical expertise, every year thousands of farmers fail to reach maximum yield potential. Over 70% of farmers own less than 5 ha in Pakistan; therefore, it is uneconomic to employ costly mechanical and chemical strategies for the control of pests in their crops. Among these pests, we eds are considered to be the major obstacle to crop production, and can ultimately result in crop failure. Traditionally, manipulation of cropping techniques was employed for the control of weeds; later on, development of synthetic chemical herbicides made it easier to control weeds in a very short time period. However, over time the increased use of herbicides has led to the development of herbicide resistant weeds. Furthermore, increasing environmental concerns, weed population shifts, and increased managerial costs have made it difficult for farmers to control these weed species within their limited economic resources. Nowadays, scientists and research organizations are being urged to provide innovative weed management solutions, with minimal ecological impacts. Studies have revealed the importance of cultural strategies for the management of weeds in different cropping systems. Research has proved that alternation of cultural practices, and selection of competitive crop cultivars, could be a possible strategy to minimize the competitiveness of weeds. Increased crop densities, narrower row spacing, intercropping and alternation in row directions are among the weed control strategies gaining rapid attention in many countries. Unfortunately, limited information is available about weed management using crop competition in Pakistan. This review article focusses on the importance of these agronomic practices in reducing the competitive potential of weeds, for their effective and appropriate management in major crops of Pakistan. It is intended to assist researchers in the design of economically viable and eco-friendly weed management strategies, which will aid in eliminating the burden of herbicides and mechanical cultivation from farmer's production costs. Highlights: Current status of weed management using crop competition in Pakistan has been reviewed. Studies revealed the importance of cultural strategies for weed management in different cropping systems. Row spacings, crop densities, competitive cultivars, and alternation in row directions need further investigations.